2016
DOI: 10.1161/atvbaha.115.306263
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of Endothelial Nitric Oxide Synthase in Perivascular Adipose Tissue of Diet-Induced Obese Mice

Abstract: induced obesity, namely uncoupling of the endothelial nitric oxide (NO) synthase (eNOS) in PVAT. Materials and MethodsMaterials and Methods are available in the online-only Data Supplement.© 2015 American Heart Association, Inc. Objective-The present study was conducted to investigate the contribution of perivascular adipose tissue (PVAT) to vascular dysfunction in a mouse model of diet-induced obesity. Approach and Results-Obesity was induced in male C57BL/6J mice with a high-fat diet for 20 weeks, and vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
209
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(234 citation statements)
references
References 48 publications
19
209
0
6
Order By: Relevance
“…The reasons for this are unclear, but increased levels of reactive oxygen species have been reported to lead to the uncoupling of eNOS resulting in the formation of perioxynitrite rather than NO. 31,48 This is supported by previous data from our laboratory showing free radical scavengers can rescue PVAT anticontractile function in human obesity 10 and the recent work of Xia et al 42 showing eNOS uncoupling within aortic PVAT from high-fat fed mice.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The reasons for this are unclear, but increased levels of reactive oxygen species have been reported to lead to the uncoupling of eNOS resulting in the formation of perioxynitrite rather than NO. 31,48 This is supported by previous data from our laboratory showing free radical scavengers can rescue PVAT anticontractile function in human obesity 10 and the recent work of Xia et al 42 showing eNOS uncoupling within aortic PVAT from high-fat fed mice.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, a recent study reported increased macrophage infiltration in the aortic PVAT of obese mice when identified using either CD68 or F4/80. 42 Eosinophils play a role in sustaining anti-inflammatory M2 macrophages within the adipose tissue, 43 and recent studies within our laboratory have shown a loss of PVAT anticontractile effect in ΔdbGATA-F2 mice, which are deficient in eosinophils. 44 We show a reduction in the number of eosinophils within PVAT in diet-induced obesity and an inverse correlation with body weight, consistent with reports in perigonadal adipose tissue from obese mice.…”
Section: Discussionmentioning
confidence: 96%
“…34 Second, diet-induced obesity caused eNOS uncoupling in PVAT by arginase-induced L-arginine deficiency. 35 Of note, obesity-induced loss of anticontractile effect of PVAT was reversed by calorie restriction. 36 Taken together, these new lines of evidence represent the therapeutic potential of targeting PVAT in the treatment of cardiovascular disease associated with vascular dysfunction.…”
Section: Perivascular Adipose Tissuementioning
confidence: 99%
“…However, mounting evidence suggests that in disease states, PVAT contributes to endothelial dysfunction, neointimal formation, atherosclerosis, and other cardiovascular diseases, including abdominal aortic aneurysms, aortic stiffness, and vasculitis [412]. Mechanistically, these effects have been linked to local inflammation, oxidative stress, and decreased nitric oxide (NO) release from endothelium along with uncoupling of endothelial NO synthase (eNOS) in PVAT [13, 14]. …”
Section: Introductionmentioning
confidence: 99%